Implementasi Efektifitas Pelvic Floor Exercise Untuk Menurunkan Frekuensi Berkemih Pada Lansia - Dila Teju, Selly Omega; Sinawang, Gabriel Wanda; Prasanto, Anastasia Nimas (Universitas Negeri Gorontalo, 2023)
Pelvic floor exercise in the elderly plays a crucial role as a simple intervention that can be independently performed at home, aiming to address the issue of increased urinary frequency due to the decline in musculoskeletal and urinary physiological functions caused by the weakening of the sphincter muscles. In this effort, the activity aims to raise awareness about the importance of pelvic floor muscle exercises to reduce urinary frequency and the risk of urinary incontinence in the elderly. The implementation of this activity focuses on the area of the Healthy Elderly Integrated Service Post (Posyandu Lansia Sehat), with the goal of directly involving the elderly in maintaining their health quality. Community service projects employ a participatory approach through lectures, debates, demonstrations, and direct re-demonstrations to expand older people's understanding of pelvic floor exercises. One method for analyzing and assessing the degree of knowledge among older people is questionnaires. Conclusion community service activities carried out in the Jelidro community regarding pelvic floor exercise to reduce urinary frequency in older people can be understood by the percentage of 74% of questionnaire results. It can be done independently at home to maintain the physiological function of the pelvic muscle.